Server Cloud Scheduling - Maack, Marten; Meyer auf der Heide, Friedhelm; Pukrop, Simon (Algorithmica)
Abstract Consider a set of jobs connected to a directed acyclic task graph with a fixed source and sink. The edges of this graph model precedence constraints and the jobs have to be scheduled with respect to those. We introduce the server cloud scheduling problem, in which the jobs have to be processed either on a single local machine or on one of infinitely many cloud machines. For each job, processing times both on the server and in the cloud are given. Furthermore, for each edge in the task graph, a communication delay is included in the input and has to be taken into account if one of the two jobs is scheduled on the server and the other in the cloud. The server processes jobs sequentially, whereas the cloud can serve as many as needed in parallel, but induces costs. We consider both makespan and cost minimization. The main results are an FPTAS for the makespan objective for graphs with a constant source and sink dividing cut and strong hardness for the case with unit processing times and delays.
Keywords: Applied Mathematics; Computer Science Applications; General Computer Science

Mincut Sensitivity Data Structures for the Insertion of an Edge - Baswana, Surender; Gupta, Shiv; Knollmann, Till (Algorithmica)
Keywords: Applied Mathematics; Computer Science Applications; General Computer Science

Kinetic Facility Location - Degener, Bastian; Gehweiler, Joachim; Lammersen, Christiane (Algorithmica)

Denesting by Bounded Degree Radicals - Blömer, J. (Algorithmica)
Keywords: Applied Mathematics; Computer Science Applications; General Computer Science

I/O-Efficient Well-Separated Pair Decomposition and Applications - Govindarajan, Sathish; Lukovszki, Tamas; Maheshwari, Anil; Zeh, Norbert (Proceedings of the 8th Annual European Symposium on Algorithms (ESA 2000), LNCS)

Strongly adaptive token distribution - Meyer auf der Heide, Friedhelm; Oesterdiekhoff, Brigitte; Wanka, Rolf (Algorithmica)

Efficient PRAM simulation on a distributed memory machine - Karp, R. M.; Luby, M.; Meyer auf der Heide, Friedhelm (Algorithmica)